Synthesis, characterization and DFT computational studies of new heterocyclic azo compounds - Almashal, Faeza; Jabar, Abeer Mohamed; Dhumad, Adil Muala (European Journal of Chemistry, 2018)
New heterocyclic azo compounds were prepared by coupling the diazonium salts with N-(4-methylphenyl)maleimide with various different sulfa compounds. The structure of heterocyclic azo compounds was determined by MS, FT-IR and 1H NMR techniques. The density function theory calculation at the B3LYP method with 6-311G(d,p) basis set is used to investigate the electronic structures of the prepared heterocyclic azo compounds. Mulliken charge distributions and HOMO-LUMO energies of the mentioned compounds have been also computed by same method and basis set.